Comparative Study of the Roles of ASEAN and the Organization of Islamic Cooperation in Responding to the Rohingya Crisis - Irawan Jati (Center for Southeast Asian Social Studies (CESASS), 2017)
Since 2012, Southeast Asia has witnessed the human rights tragedy of the Rohingya people of Myanmar. Hundreds of thousands of Rohingya have been displaced from their homes and traveled to refugee facilities in Myanmar and Bangladesh, while others have been stranded on the Andaman Sea. The Rohingya crisis is perhaps the most horrific human rights tragedy after the crisis in Vietnam in the 1970s. As the crisis has developed, international communities, including ASEAN and the Organization of Islamic Cooperation (OIC), have responded to the crisis. As the main regional organization, ASEAN has been hoped to elucidate the crisis tactically through peaceful means. OIC, meanwhile, has been expected to join humanitarian action using a diplomatic approach to other international humanitarian bodies, including the UNHCR. However, it is obvious that ASEAN's response to the crisis has been limited to diplomatic oration and failed to prevent a wider crisis. For OIC, its humanitarian solidarity has lacked access to the target community. Therefore, this paper would like to attempt a comparative analysis to describe the central inquiry; how have ASEAN and OIC responded to the Rohingya crisis? This analysis involves studying ASEAN and OIC publications and related references. The initial argument of this paper is that both organizations have given reasonable responses to the crisis, but have been unable to halt its advance.